A survey of the empirical evidence on PWYW pricing - Matthias Greiff; Henrik Egbert (Philipps-University Marburg, School of Business and Economics, 2016)
We review a large number of empirical studies on Pay-What-You-Want (PWYW) pricing. We distinguish between laboratory experiments, field experiments, survey experiments and case studies. Based on this survey we identify the following two gaps in the recently flourishing literature on PWYW pricing: (1) studies on PWYW pricing for goods with high cost, and (2) studies on the long-term effects of PWYW pricing.
Keywords: C90; D12; D49; M21; M30; 330; Pay-What-You-Want; PWYW; pricing mechanism; survey; empirical studies